2021
DOI: 10.1111/jam.14997
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and genomic analysis of vB‐AhyM‐AP1, a lytic bacteriophage infectingAeromonas hydrophila

Abstract: Aims: Aeromonas hydrophila is a zoonotic pathogen displaying resistance to multiple antibiotics. Here, we aim to develop a candidate biocontrol agent against A. hydrophila. Methods and Results: In this study, we isolated and characterized the phage vB-AhyM-AP1 from sewage. It showed lytic activity against A. hydrophila strains. One-step growth curve revealed that the latent period lasted for 40 min. The burst size of one lytic cycle was 1413 PFU per infected cell. Temperature stability studies showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Ib_pec2 exhibited a burst size of 893 pfu/ml. Similar large burst sizes were also reported in podoviridae phages [22], myoviridae phages [23], and Autographiviridae [24]. The results of one-step growth curve depend upon the media, incubation conditions, the number of receptors in bacteria, and so on [23].…”
Section: Discussionsupporting
confidence: 76%
“…Ib_pec2 exhibited a burst size of 893 pfu/ml. Similar large burst sizes were also reported in podoviridae phages [22], myoviridae phages [23], and Autographiviridae [24]. The results of one-step growth curve depend upon the media, incubation conditions, the number of receptors in bacteria, and so on [23].…”
Section: Discussionsupporting
confidence: 76%
“…The majority of marine phages are highly host-specific [ 232 , 233 , 234 ], and about 73% lyse only the original host bacterium [ 234 ]. Although phages with a broad host range are hard to find, some examples of virulent phages have shown some promise for therapeutic use in aquaculture, infecting strains of several bacterial species [ 180 , 181 , 217 , 235 , 236 ] and genera [ 92 , 237 ] ( Table S2 ). Liu et al (2020) reported that the isolated phages had a relatively broad infectivity spectrum against A. hydrophila and showed the potential to infect A. veronii , A. caviae and A. bestiarum [ 236 ].…”
Section: Challenges Associated With the Use Of Phages To Control ...mentioning
confidence: 99%
“…A. hydrophila phages vB-AhyM-AP1 and pAh-1 presented high burst sizes (1413 and 608 PFU/host cell, respectively); however, the latent period of phage vB-AhyM-AP1 (40 min) is higher than that of phage pAh-1 (15 min) [ 211 , 235 ] ( Table S2 ). Phage AhyVDH1 infected A. hydrophila producing 274 PFU/host cell [ 214 ], TG25P (79 ± 11.9 PFU/host cell) [ 212 ]; Akh-2 (139 PFU/host cell) [ 149 ] and AHP-1 (97 PFU/host cell) [ 181 ].…”
Section: Challenges Associated With the Use Of Phages To Control ...mentioning
confidence: 99%
See 2 more Smart Citations